KMA Marketing Sdn Bhd: a study on the effetiveness of China truck's promotion / Siti Norashikin Kamarudin - Kamarudin, Siti Norashikin (2006)
This research is mainly about the study on the effectiveness of China Truck's promotion carried out by KMA Marketing Sdn Bhd. The objectives of this research are to identify the effectiveness of China Truck's promotion carried out by KMA Marketing Sdn Bhd, to find out the factors that contribute to the effective or ineffective of their China Truck's promotion and to recommend some improvement to increase the ineffective of China Truck's promotion. The first chapter contains the introduction and background of study that include scope of study, problem statement, research objectives, significance of study, research questions, the limitation of study and the definition of terms. The second chapter is literature review. Literature review is the information that is the researcher obtained from books, journal and some of the printed media to support this research. The information must be relevant with the topic of research. The third chapter is research methodology. Research methodology is explains the method that has been used to analyze the study. The researcher used primary and secondary data to obtain the information. The study was conducted among 130 respondents in Kota Kinabalu area by using convenience sampling technique. The results were analyzed and computed for frequency and cross tabulation. Based on the findings, several recommendations are been proposed to the company. The recommendations are in order to improve the company's promotion, especially for China Truck.